Rule and rupture : state formation through the production of property and citizenship - Lund, Christian; Eilenberg, Michael (Development and change (Unnumbered), 2017)
Rule and Rupture - State Formation Through the Production of Property and Citizenship examines the ways in which political authority is defined and created by the rights of community membership and access to resources.-Combines the latest theory on property rights and citizenship with extensive fieldwork to provide a more complex, nuanced assessment of political states commonly viewed as "weak," "fragile," and "failed"--Contains ten case studies taken from post-colonial settings around the world, including Cambodia, Nepal, Indonesia, Afghanistan, Rwanda, Somalia, Democratic Republic of Congo, Colombia, and Bolivia -Characterizes the results of societal ruptures into three types of outcomes for political power: reconstituted and consolidated, challenged, and fragmented -Brings together exciting insights from a global group of scholars in the fields of political science, development studies, and geography.